Business and professional communication : keys for workplace excellence - Quintanilla, Kelly M.; Wahl, Shawn T. (Thousand Oaks, Calif. : SAGE, 2011)
This text presents an exciting new approach to teaching the core concepts and the techniques of business and professional communication, and is organized by the sequence of experiences readers will face as they transit from student to professional, and from interviewee to team member to leader.
Includes bibliographical references and index.
rua 04/11/13, ijb 11/04/2019
Loans
Keywords: Business communication; Professional communication; Workplace excellence